Homo Economicus as the Basis of "Asgardia" Nation State in Space: Perspective of Educational Technologies - Roman Oleksenko; Lidiia Fedorova (International Society of Philosophy and Cosmology, 2017)
This paper considers the perspective of using the concept of Homo economicus as a cultural ideal. According to the authors, modern educational technologies must be directed to achieve this cultural ideal. The concept of education is understood by the authors in the classical interpretation, as deliberately molding human character. The authors use the historical method, formalization method and others in this paper. It has been proved that all constructive criticism of old interpretations of the concept of Homo economicus does not deny the possibility of using this term in the foreseeable future. On the contrary, criticism gives new interpretations of Homo economicus, which open up new prospects for using this concept, in particular, as a cultural ideal for educational technologies when creating the "Asgardia" nation state in space.